The Effect of Pair Passing and Individual Passing Drills on the Underhand Volleyball Passing Learning Outcomes of 10th Grade Students at SMKN 1 Koto Baru - Janiva, Yesi Wina; Prasetyo, Dian Estu; Sukron, Muhammad (TOFEDU: The Future of Education Journal, 2025)
Physical education is an educational process that uses physical activity as a medium to achieve educational goals. Physical education is "education through physical activities/movements" through participation in physical activities, where students can acquire skills and knowledge, develop aesthetic appreciation, enhance general skills and positive attitudes, as well as improve physical fitness. The objective of this study was to determine the effect of pair passing and individual passing drills on the underhand volleyball passing learning outcomes of 10th-grade students at SMKN 1 Koto Baru. This research is a quantitative study using an experimental method approach. The results obtained using this method indicate that the hypothesis is accepted, meaning there is an effect of pair passing and individual passing drills on underhand volleyball passing learning outcomes. The significance value obtained is 0.784, which is greater than the required threshold of 0.05.